Proceedings of 9th International Symposium on Graphic Engineering and Design 2018
DOI: 10.24867/grid-2018-p11
|View full text |Cite
|
Sign up to set email alerts
|

Printability Characteristics of Paper Made From a Japanese Knotweed

Abstract: Cereal straw and bagasse are presently the leading non-wood plants used in production of paper, though many fast-growing perennial plants have been studied for their suitability for paper manufacturing, too. In the present study the use of Japanese knotweed, as one of the most invasive alien plant species in Slovenia, as alternative raw material for papermaking is demonstreted. Paper was made of 55% Japanese knotweed and sulfate cellulose produced from 60% eucalyptus and 40% conifer fiber. The paper with the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Also, the roughness Bendtsen [3] of the paper is primordial for the absorption and the spreading of inks, and also for determining the amount of coating. Relation could be considered as to the scale of roughness to properties of paper such as gloss and pick resistance [4,5]. The effect of the pH value could be examined as to its influence on the optical and morphological properties of a copy paper sample.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the roughness Bendtsen [3] of the paper is primordial for the absorption and the spreading of inks, and also for determining the amount of coating. Relation could be considered as to the scale of roughness to properties of paper such as gloss and pick resistance [4,5]. The effect of the pH value could be examined as to its influence on the optical and morphological properties of a copy paper sample.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing, as satellites are called, is already being used in forestry, agriculture, and ecology because it is a less expensive technique compared to field reconnaissance methods (Figure 1). Preliminary research by Lavrič [6] has shown that the invasive Japanese knotweed could be used as a cheap local raw material in the paper industry, but in order to achieve good printability properties of the paper, mainly the fiber processing needs to be improved. Kim et al, isolated cellulose nanofibers from pulps of a tall goldenrod (Solidago altissima L.), an invasive plant in Korea, using electron beam irradiation [7].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…DC., and Hibiscus cannabinus L., and a reed species were investigated in the laboratory for their properties for pulp and paper production, and the results suggested that the plant species studied would be ideal sources of raw material for the pulp and paper industry. In the project APPLAUSE, seven IAPS Preliminary research by Lavrič [6] has shown that the invasive Japanese knotweed could be used as a cheap local raw material in the paper industry, but in order to achieve good printability properties of the paper, mainly the fiber processing needs to be improved. Kim et al, isolated cellulose nanofibers from pulps of a tall goldenrod (Solidago altissima L.), an invasive plant in Korea, using electron beam irradiation [7].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Various non-wood plant agricultural sources have already been considered as potential pulp and paper feedstocks in the past (Ogbonnaya et al 1997;Gonzalo et al 2017;Saeed et al 2017a;Gülsoy and Şimşir 2018;Lavrič et al 2018). In addition, energy crops, and their residues, including Miscanthus spp.…”
Section: Introductionmentioning
confidence: 99%